STUDI PERBAIKAN THD PADA MULTILEVEL INVERTER SATU FASA TUJUH TINGKAT - Effendi (Politeknik Aceh, 2018)
Multilevel Inverter (MLI) single phase seven level in this research is constructed by using cascaded H-Bridge modification which consists of three independent DC sources in form of 9 Volt batteries which arranged in series where each source separated by MOSFET that used as switch and uses three diodes and furthermore connected with H-Bridge circuits which serves to reverse the direction of the electric current to producing alternating voltage on the resistif load. MOSFET switching circuits was designed by using SPWM Method that has modified from previous Researchers, by using the operational amplifier component that used as comparator between the reference wave in form of sinusoidal wave which having maximum amplitude 9 volts with carrier voltage that has been modified from DC sources as many as three (1.5 Volt, 4.5 Volt and 7.5 Volt) and use analog and digital electronic components which function to activate the gate of each MOSFET in the power circuits. THD that generated in this study by 11.6% while the research [3] produces THD 18.07%, and 18.40% for methods PD (Phase Disposition) PWM, APOD (Altenative Phase Opposition Disposition) PWM, thus this system is able to produce better THD than previous research